FILED OF KAREN ETHNIC BEFORE THE ADVENT OF MODERNITY: THE CASE OF A KAREN COMMUNITY IN THE WEST OF THAILAND - Netawong, Jesada; Doaudom, Parichai (Journal of Buddhist Anthropology, 2022)
The objectives of this research article were to study the social context, environment, and culture considered as the field of the Karen ethnicity before the advent of modernity in a Karen community in the western region of Thailand. It presents the case study of Ban Noen Nam Fa, a Karen community that has the social context, environment, and culture of the Karen community before the advent of modernity in the community as the field of the Karen ethnicity according to Bourdier’s concept of field, developed under the pre-modern paradigm. The results have revealed the social context, environment, and culture before the advent of modernity, which can be traced back to their Karen ancestry about a hundred years ago, according to their oral history. These can be explained by the concept of field, which points to structure, rules, institutions, and capital that have existed in the field of Karen ethnicity, including 1) Rules tied to the beliefs in supernatural powers which established the rules of this field. 2) Rituals/practices following the rules and beliefs in everyday life of the Karen people 3) Bearers of rules and traditions and institutions upholding these rules 4) The transmission of beliefs, rules, rituals, and practices as knowledge through stories, local lore, moral teachings, and actions.